HUMAN CAPITAL AND INCLUSIVE GROWTH IN SUB-SAHARAN AFRICA: THE CASE FOR HEALTH - AYODEJI , ABIODUN OWOPETU; OVIKUOMAGBE , OYEDELE; SHERIFFDEEN, TELLA (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
This paper employs the Pooled Mean Group (PMG) technique to investigate the nexus between human capital development and inclusive growth across 20 sub-Saharan African (SSA) countries from 2000 to 2021. The results reveal that human capital development indicators positively influence the inclusive growth index in both the short and long run, except for public health expenditure, which shows a significant negative impact. The study finds that economic adjustments toward equilibrium occur within a year, as indicated by the error correction mechanism. Policy recommendations include increasing government spending on health, improving citizen empowerment, reducing corruption, and upholding the rule of law to ensure life expectancy translates into equitable growth.